Is Neutrophil/Lymphocyte Ratio Associated with Subclinical Inflammation and Amyloidosis in Patients with Familial Mediterranean Fever?. (20th June 2013) - Uslu, Ali Ugur; Deveci, Koksal; Korkmaz, Serdal; Aydin, Bahattin; Senel, Soner; Sancakdar, Enver; Sencan, Mehmet
Abstract : Background . The purpose of the present study is to determine the association between neutrophil/lymphocyte ratio and both subclinical inflammation and amyloidosis in familial Mediterranean fever. Methods . Ninety-four patients with familial Mediterranean fever and 60 healthy volunteers were included in the study. Of the patients, 12 had familial Mediterranean fever related amyloidosis. The neutrophil/lymphocyte ratio of the patients was obtained from the hematology laboratory archive. Results . The neutrophil/lymphocyte ratio was significantly higher among persons with familial Mediterranean fever compared to healthy individuals (P < 0.0001 ). Also, neutrophil/lymphocyte ratio was significantly higher in patients with amyloidosis than in amyloidosis-free patients (P < 0.0001 ). Since NLR was evaluated in nonamyloid and amyloid stages of the same patient population (type 1 phenotype), we obtained significant statistical differences (1.95 ± 0.30 versus 2.64 ± 0.48, P < 0.05, resp.). With the cutoff value of neutrophil/lymphocyte ratio >2.21 and AUC = 0.734 (P = 0.009 ), it was a reliable marker in predicting the development of amyloidosis. Conclusion . The neutrophil/lymphocyte ratio, an emerging marker of inflammation, is higher in patients with familial Mediterranean fever in attack-free periods. The neutrophil/lymphocyte ratio may be a useful marker in predicting the development of amyloidosis.